(untitled) - Woronoff, Jon (Tokyo, 1990)
This book introduce about Japanese-style management, Japanese companies, industrial policy, economic progress, eduacation, quality of life...
Keywords: Chất lượng cuộc sống,Quality of life; Nhật Bản,Japan